2004
DOI: 10.1354/vp.41-3-269
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Estrogen Receptor β in Normal and Tumoral Canine Mammary Glands

Abstract: To date, two isoforms of estrogen receptors (ER) have been identified, cloned, and characterized from several species, estrogen receptor-alpha (ERalpha) and estrogen receptor-beta (ERbeta). Although the presence of ERalpha has been demonstrated in normal and tumoral canine mammary tissues, the issue of ERbeta expression has not been addressed in the dog. In this study, we have analyzed the expression of ERbeta in formalin-fixed, paraffin-embedded tissue samples of nonaltered mammary gland, 30 malignant (six co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 10 publications
4
21
2
3
Order By: Relevance
“…In the bitch, a study has demonstrated that ERβ is expressed in normal and neoplastic mammary glands, with higher expression in BMT than in MMT. Furthermore, the expression is higher in complex and mixed histological types of MMT (which are associated with a favorable prognosis) compared to simple types (Martín de las Mulas et al, 2004), showing that ERβ expression may be a favorable prognostic factor.…”
Section: Prognosismentioning
confidence: 97%
“…In the bitch, a study has demonstrated that ERβ is expressed in normal and neoplastic mammary glands, with higher expression in BMT than in MMT. Furthermore, the expression is higher in complex and mixed histological types of MMT (which are associated with a favorable prognosis) compared to simple types (Martín de las Mulas et al, 2004), showing that ERβ expression may be a favorable prognostic factor.…”
Section: Prognosismentioning
confidence: 97%
“…Martín De las Mulas and coworkers [9] studied the immunohistochemical detection of ER β in normal and tumor-affected canine mammary glands. They reported the expression of ER β in the nuclei of acinar and ductal epithelial cells and some basal myoepithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression for the oestrogen (ER) and progesterone (PR) receptors is related to a better prognosis while the positivity of the CK5 receptor is related to a worse prognosis, in both canines and humans with mammary carcinomas (Terra et al 2012, Horta et al 2012, Figueiroa et al 2012. In canines, the expression of ER is higher in benignant tumors than in malignant ones and is also higher in complex and mixed tumors in comparison with simple sub-types (De Las Mulas et al 2004).…”
Section: Introductionmentioning
confidence: 99%